Manzuma gen. nov., a new aelurilline genus of jumping spiders (Araneae, Salticidae) - Azarkina, Galina N. (European Journal of Taxonomy, 2020)
A new jumping spider genus, Manzuma gen. nov. (Salticidae Blackwall, 1841), is described, type species is Manzuma nigritibia (Caporiacco, 1941). Aelurillus reconditus Wesołowska & van Harten, 1994 is synonymized with Rafalus nigritibiis (Caporiacco, 1941). Four new combinations are proposed: M. jocquei gen. et comb. nov. (ex Aelurillus), M. kenyaensis gen. et comb. nov. (ex Langelurillus), M. lympha gen. et comb. nov. (ex Rafalus) and M. nigritibia gen. et comb. nov. (ex Rafalus). Three species, M. botswana gen. et sp. nov. (♂♀, Botswana and Republic of South Africa), M. petroae gen. et sp. nov. (♂♀, Republic of South Africa) and M. tanzanica gen. et sp. nov. (♂, Tanzania), are described. The male of M. kenyaensis gen. et comb. nov. and female of M. lympha gen. et comb. nov. are described for the first time. A new aelurilline synapomorphy is proposed. Identification key for males is provided.